Student Developmental Needs Based Parent Partnership: A Case Study of Qilun Elementary School in Minhang District, Shanghai - Lichi, Jiacheng; Wang, Peiying; Chen, Zhongxian (International Journal about Parents in Education, 2023)
This case study reconsiders the value of parent partnerships from the perspectives of educational equity and quality in China, and develops a framework to discuss the relationship between student development and parent partnerships. The paper seeks to find out whether it is possible for disadvantaged parents to help a struggling school to reform itself through parent partnership. The research applies qualitative and quantitative research methods to explore the value of promoting student development with diversified parent/school activities. Research findings suggest that parent partnership in the case school have successfully provided a safe and healthy environment, abundant and diverse courses, student-based teaching and learning, and rich school lives for students. They also involve in school decision-making and create a better parent-child relationship.